Penerapan Analisis Matriks dalam Penyelesaian Masalah Matematika Bisnis dan Ekonomi: Penelitian - Muhammad Yusuf Harahap; Febyana Br Sembiring; Gina Ami Sefi Br Ginting; Lamtiar Sinaga; Pia Lestari Br Saragih; Romagiano Machario S. Sembiring; Reginta Br Barus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study examines input and output analysis as a form of matrix application that functions as a mathematical model to understand the interrelationships between activities in an economy. Learning and mastery of mathematics are crucial because many problems require the ability to formulate concepts mathematically through modeling. This study uses the Matrix Inverse Method and the Gauss-Jordan Elimination Method. The calculation process is performed using MATLAB (Matrix Laboratory) software, which facilitates efficient handling of mathematical operations.